Analisis Perubahan Penggunaan Lahan Di Jazirah Leitimur Pulau Ambon - Johanis P Haumahu (Agrologia, 2014)
Land use is the element that changes very dynamic area. This is due to various human activities depend on the elements of this land. One of the most influential factor in the speed of change in land use or land use change is the increase of population in an area. Fulfillment of human needs (food, clothing and shelter) is influenced by the availability of land. This study aims to identify and analyze the rate of land conversion in conjunction with the growth of population in the peninsula Leitimur Ambon Island. The method used is descriptive with population growth comparing data (statistics) with patterns of changes in land use map data obtained from Ambon city land use remote sensing and data. The rate of population growth in the city of Ambon Leitimur Peninsula in the last 10 years (2000-2010) shows the percentage figures are quite high, 179,78 percent and with a population density of 1.145,436 inhabitants/km2. Land conversion that occurred in the Peninsula Leitimur of the Year 1984 - 2010 are as follows: (1) forest becomes 3.008,06 to  1.057,69 ha; (2) be mixed farms 5.533,46 to 8.671,97 ha; (3) vacant land 0,00 ha to 94.67 ha; (4) settlements be 2.768,58  to 3.129,83 ha; (5) bushes and reeds 4.113,39  to 1.372,58 ha;  and (6) other use 0.00 ha to 1.150,75 ha. From these results show that the rate of change (conversion) of land is directly proportional to the growth of population.